Analysis of the Trichuris suis excretory/secretory proteins as a function of life cycle stage and their immunomodulatory properties. Issue 1 (December 2018) - Leroux, Louis-Philippe; Nasr, Mohamad; Valanparambil, Rajesh; Tam, Mifong; Rosa, Bruce; Siciliani, Elizabeth; Hill, Dolores; Zarlenga, Dante; Jaramillo, Maritza; Weinstock, Joel; Geary, Timothy; Stevenson, Mary; et al.
Abstract Parasitic worms have a remarkable ability to modulate host immune responses through several mechanisms including excreted/secreted proteins (ESP), yet the exact nature of these proteins and their targets often remains elusive. Here, we performed mass spectrometry analyses of ESP (TsESP) from larval and adult stages of the pig whipwormTrichuris suis (Ts) and identified ~350 proteins. Transcriptomic analyses revealed large subsets of differentially expressed genes in the various life cycle stages of the parasite. Exposure of bone marrow-derived macrophages and dendritic cells to TsESP markedly diminished secretion of the pro-inflammatory cytokines TNFα and IL-12p70. Conversely, TsESP exposure strongly induced release of the anti-inflammatory cytokine IL-10, and also induced high levels of nitric oxide (NO) and upregulated arginase activity in macrophages. Interestingly, TsESP failed to directly induce CD4+ CD25+ FoxP3+ regulatory T cells (Treg cells), while OVA-pulsed TsESP-treated dendritic cells suppressed antigen-specific OT-II CD4+ T cell proliferation. Fractionation of TsESP identified a subset of proteins that promoted anti-inflammatory functions, an activity that was recapitulated using recombinantT. suis triosephosphate isomerase (TPI) and nucleoside diphosphate kinase (NDK). Our study helps illuminate the intricate balance that is characteristic of parasite-host interactions at the immunological interface, and further establishes the principle that specific parasite-derived proteins can modulate immune cell functions.